School dropout and substance use: Consequence or predictor? - P. Valkov (Trakia Journal of Sciences)
Several national studies report that students decide to drop out of school because of various reasons. Furthermore, there are ethnic variations in the causes of early school leaving. In the present study, the relationship between reasons for school dropout and substance use was investigated. A review of different articles was undertaken to determine whether existing research could provide evidence and a better understanding of the relationship between dropping out of high school and the use of substances such as tobacco, alcohol, cannabis/marijuana and other illicit drugs. School dropout often co-occurs with substance use. The aim of this article is to examine the type of the relationship between school dropout and substance use disorders. A few research results show that school dropout is a predictor of substance use. According to other authors, however, relationship of these two phenomena is the opposite: substance use causes school dropout. A third possible explanation supposes that the relationship between school dropout and substance use is not causal, but rather both are caused by a third variable. In conclusion, author suggests expanding the research on the relationship between substance use and school dropout in order to improve prevention of these two problems. Recommendations are given for ways in which the reasons for dropout and substance use can help to inform families, educators and mental health providers.